Adolescents Who Report Being Involved in Physical Fights in Mauritius: A Cross-Sectional Study of Socio-Demographic and Behavioral Correlates - Olumide Abiodun; Michael Lowery Wilson; Masood Ali Shaikh (MDPI AG, 2021)
Background: violence among young people, including physical fighting, is a crucial global public health concern. There is a scarcity of evidence directed at understanding the prevalence and associated factors for physical fights among adolescents in Mauritius. This study aimed to examine the prevalence physical fighting in schools and the demographic characteristics that are associated with the phenomenon. Methods: we conducted a cross-sectional analysis of nationally representative data from Mauritius with the aim of examining the 12-month prevalence of physical fighting and frequencies of related individual and social-level characteristics. We further measured the association between physical violence and adolescent parameters using binary logistic regression analyses. Results: the participants were predominantly females (53.49%) with a mean age of 14.91 (1.47) years. Within the preceding twelve months, 15.74% of the participants reported being involved in physical fights. Among other factors, the male gender (OR = 2.6, 95% CI (1.87, 3.62)), food deprivation (OR = 2.46, 95% CI (1.41, 4.32)), bullying victimization (OR = 2.81, 95% CI (2.12, 3.73)), and cigarette use (OR = 2.07, 95% CI (1.34, 3.19)) increased the likelihood of physical fighting. The other associated factors were loneliness (OR = 1.65, 95% CI (1.11, 2.43)), physical activity (OR = 1.52, 95% CI (1.09, 2.12)), early sexual debut (OR = 2.15, 95% CI (1.17, 3.95)), and alcohol use (OR = 1.56, 95% CI (1.11, 2.21)). Conclusions: physical violence is frequent among adolescents in Mauritius; however, a comparison with previous findings in similar sub-Saharan countries suggests a reducing trend. Advocates, policymakers, and other critical stakeholders need to consider the relevant demographic and behavioral factors in formulating strategies and designing public health interventions for the prevention and control of physical violence among adolescents.